ANALYSIS OF DATA PROTECTION MECHANISMS IN CLOUD ENVIRONMENTS - ВАРАНІЦЬКИЙ, Д. В.; РОЗКОЛОДЬКО, О. О.; ЛЮТА, М. В.; ЗАХАРОВА, М. В.; ХОТУНОВ, В. І. (Technologies and Engineering, 2024)
Purpose: Improving the security of cloud technologies. Analysis of information protection mechanisms in cloud environments and pointing out of their peculiarities. Searching for the most effective mechanism for protecting information, which is stored in cloud environments. Improving the security of cloud technologies will allow more people and organizations, for whom security is very important, to use such technologies. Due to the increase in the number of companies and institutions using cloud environments for the storage and exchange of internal data, there is a need for improved levels of security of this system. Methodology: The article examines the peculiarities of data protection mechanisms in cloud environments. The analysis is conducted and the main properties and functions are pointed out. These mechanisms are considered and the most effective one is chosen. Findings: The main mechanisms of protection, such as encryption, data protection during transmission, authentication and isolation of users, are researched. The peculiarities of these mechanisms are pointed out. Each of these mechanisms has strengths and certain risks of information loss. To better understand the principles of data protection mechanisms against dangers the system of demonstration the effectiveness of threats to certain types of data and mechanisms for counteracting dangers is presented. The protection mechanisms demonstrate the need to create a reliable system of security and protection of information in cloud environments. The use of cloud technologies for information storage must be accompanied by regular improvement of the security system, as well as the use of the most reliable mechanism. Scientific novelty: The presented mechanisms of protection can be the basis for the development of new ways to protect information in the cloud environment. It will allow more people to use cloud technologies without the risk of data loss. Practical value: According to the results of the analysis, the existing mechanisms for protecting data in the cloud environment are defined; the mechanisms for providing security to cloud technologies, building a scheme for user interaction, key management servers and a cloud server are compared.